The status of studies on the mechanism of microcirculatory dysfunction in the process of diabetic kidney injury - Zeng Wu; Yu Gao; Chun-yue Zuo; Xiao-rong Wang; Xiao-han Chen; Xiao-hong Zhou; Wei-juan Gao (Diabetology & Metabolic Syndrome)
Abstract Diabetic nephropathy (DN) is one of the most common and serious microvascular complications of diabetes mellitus (DM) and is the main cause of end-stage renal disease. Endothelial dysfunction caused by persistent hyperglycemia occurs at the initial stage of vascular disease. Moreover, persistent hyperglycemia is also a critical factor causing renal microcirculatory dysfunction. In recent years, many studies have confirmed that chronic hypoxia caused by microcirculatory dysfunction is one of the main mechanisms of kidney injury in patients with DM. Similarly, microcirculatory dysfunction damages renal tissue through interactions with other pathophysiological processes, thereby promoting the occurrence and development of DN. Thus, this article reviews the pathogenesis of renal microcirculatory dysfunction in DM and its interaction with stress, energy metabolism, and immunologic inflammation. Furthermore, a new idea was proposed to analyze the mechanism of kidney injury in DM from the perspective of microcirculatory dysfunction.